Risky Lifestyles, Low Self-control, and Violent Victimization Across Gendered Pathways to Crime - Turanovic, Jillian J. (Journal of quantitative criminology, 2015)
Objectives The present study addresses whether unique or general processes lead to victimization across gendered pathways to crime. Specifically, the effects of low self-control and risky lifestyles—specified as various forms of offending and substance abuse—on violent victimization across developmental typologies for both men and women are examined. Methods Using data from three waves of the National Longitudinal Study of Adolescent Health, a two-stage cluster analysis is used to identify taxonomic groups for males and females that represent different pathways to crime. Multivariate negative binomial regression models are estimated to assess whether both self-control and risky lifestyles (e.g., criminal offending) are significant predictors of general forms of violent victimization across each identified cluster. Results Low self-control and risky lifestyles significantly predict violent victimization across each of the taxonomic groups identified in the data, suggesting that these causal processes are universal rather than unique to any particular gendered pathway. Conclusions Although inferences cannot be made for types of victimization beyond those observed in the study (e.g., intimate partner violence and sexual assault), the findings lend credence to the notion that self-control and risky lifestyles are critical to the study of violent victimization among men and women following different gendered pathways.